Effect of Caparis spinosa root extract on promastigotes and amastigotes of Leishmania major - Shemshadi, Bahar; Ranjbar-Bahadory, Shahrokh; Ahmadi, Hossein (Archives of Advances in Biosciences, 2015)
This study was carried out to identify the efficacy of Caparis spinosa root extract on promastigotes and amastigotes of Leishmania major. Caparis spinosa extracts were prepared. Promastogotes of L.major (1×106 parasites/ml)were incubated at 26 ºC for 24,48 and 72hours in fresh medium(NNN), in absence or presence of different concentrations (0.1,0.3,0.5,0.7,0.9 mg/ml) of Caparis spinosa methanolic root extract. It was determined that anti-protozoal activity of Caparis extract (0.9 mg/ml) was similar to glucantime as a gold standard drug (p<0.05) and both were able to kill 97.8 % of promastigotes after72 hours. Microscopic observation showed that mainly complete lyses of promastigotes after treating with0.9 mg/ml of Caparis spinosa for72hours. Higher extract concentrations had more effect on promastigote population (p<0.05). It was demonstrated that Caparis sponosa root extract has positive effect on amastigotes of leishmania major. It was determined 0.7 mg/ml and 0.9 mg/ml Caparis root extract concentrations were more effective than other concentrations on amastigots of Leishmania in ulcers. The mean of ulcer size of the mice that received 50 µl of 0.7 mg/ml and 0.9 mg/ml Caparis root extract were less than mice receiving 0.1, 0.3 and 0.5. The mean of ulcer size of the mice that received 50 µl of 0.9 mg/ml Caparis spinosa root extract were significantly smaller than control group after six weeks(p<0.05) ,but the mean of ulcer size in mice which had been received glucantime (150 mg/ml)and Caparis root extract were not significantly different (p>0.05). The results were suggestive that Caparis root extract had significantly similar effect in reduction of ulcer size as compared to glucantime (p<0.05).